2019
DOI: 10.14744/nci.2019.70893
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hyperventilation on Seizure Length and Cerebral Oxygenation during Electroconvulsive Therapy

Abstract: E lectroconvulsive shock is applied to one or both cerebral hemispheres to initiate a seizure. Variables of this shock include stimulus pattern, amplitude and duration. The aim of electroconvulsive therapy (ECT) is to create a therapeutic generalized seizure for 25-60 seconds [1]. Routine use of general anesthesia to induce unconsciousness and to prevent the damage by neuromuscular blockade raised interest in ECT.Seizure activity is characteristically associated with prolonged sympathetic discharge following a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Several case reports have demonstrated severe morbidity and even mortality in ECT patients [10]. Therefore, it is necessary to maintain hemodynamic stability during and after the procedure [11,12]. So far, several studies have been performed to maintain hemodynamic stability in ECT patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several case reports have demonstrated severe morbidity and even mortality in ECT patients [10]. Therefore, it is necessary to maintain hemodynamic stability during and after the procedure [11,12]. So far, several studies have been performed to maintain hemodynamic stability in ECT patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that a laryngeal mask could be a first-line option to manage airway and ventilation in ECT because of its minimal leaks, better airway control, and better ventilation features [ 8 , 9 ]. In practice, facemask ventilation is frequently used due to convenience but is often criticized because it cannot effectively provide airway security.…”
Section: Introductionmentioning
confidence: 99%